Two new genera of tube-making spittlebugs (Hemiptera: Machaerotidae: Enderleiniini) - Bell, Adam J.; Cryan, Jason R. (Zootaxa, 2013)
Two new monotypic spittlebug genera and their type species in the family Machaerotidae, subfamily Enderleiniinae, are described and illustrated: Labramachaerota korupa gen. & sp. n. (with type locality in Cameroon) and Kyphomachaerota maaia gen. & sp. n. (with type locality in Sarawak, Malaysia).